Nedmonteringen av försvaret på Gotland - En analys av beslutet att avveckla Regemente P 18 under 2004 - Broman,Fanny (2025)
This study demonstrates how political decisions are contextually bounded by prevailing perceptions of reality. Even strategic choices tend to be shaped more by recent events than by long-term analysis. Gotland, located in the middle of the Baltic Sea, is today considered a key strategic area for NATO. Historically, the island has played an important military role, and this study examines its contemporary relevance through the lens of policy and defense decision-making. The study aims to understand the logic behind the 2004 decision to decommission the P 18 regiment on Gotland and its subsequent return, analyzing how strategic defense decisions are made under perceived security conditions. Drawing on primary material and policy documents from 2004 to 2025, the study applies Graham Allison’s three decision-making models to explore how policy processes unfold. The case of the Swedish P 18 regiment - its decommissioning and subsequent reestablishment - serves as a focused example of how political logic often emphasizes quick, visible responses to emerging threats, rather than structural or long-term preparedness. Despite the limited time frame, the case reveals recurring patterns of delayed response, organizational friction, and reactive decision-making. These findings not only validate the relevance of Allison’s framework for this context but also offer insights into broader policy challenges in times of security uncertainty. The study contributes to our understanding of how defense policy is shaped-and constrained-when strategic environments change rapidly.
Keywords: Gotland; Policy failure; Regemente P 18; Försvarsbeslut 2004; Graham Allison